2015
DOI: 10.1080/00207179.2015.1078912
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental performance similarities between individual pitch control strategies for wind turbines

Abstract: The use of blade individual pitch control (IPC) offers a means of reducing the harmful turbine structural loads that arise from the uneven and unsteady forcing from the oncoming wind. In recent years two different and competing IPC techniques have emerged that are characterised by the specific loads that they are primarily designed to attenuate. In the first instance, methodologies such as single-blade control and Clarke Transform-based control have been developed to reduce the unsteady loads on the rotating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…We begin by considering the single‐blade formulation of an IPC controller, shown in Figure . The single‐blade formulation is chosen for simplicity, but the results in this paper extend to fixed frame of reference IPCs, owing to the performance equivalence results established in Lio et al The single‐blade model is represented by a transfer function Gfalse(sfalse)scriptR, where s is a complex variable, and scriptR is the space of real‐rational transfer functions with 1 input and 1 output. This transfer function relates the IPC blade pitch‐angle input u IPC to the measurement ytrueM˜ of the perturbation flap‐wise bending moments trueM˜ at the blade root.…”
Section: Performance Limitation Of Existing Ipc Architecturesmentioning
confidence: 99%
“…We begin by considering the single‐blade formulation of an IPC controller, shown in Figure . The single‐blade formulation is chosen for simplicity, but the results in this paper extend to fixed frame of reference IPCs, owing to the performance equivalence results established in Lio et al The single‐blade model is represented by a transfer function Gfalse(sfalse)scriptR, where s is a complex variable, and scriptR is the space of real‐rational transfer functions with 1 input and 1 output. This transfer function relates the IPC blade pitch‐angle input u IPC to the measurement ytrueM˜ of the perturbation flap‐wise bending moments trueM˜ at the blade root.…”
Section: Performance Limitation Of Existing Ipc Architecturesmentioning
confidence: 99%
“…The transform‐based IPC techniques involve coordinate mappings on the pitch inputs, which complicate the constraint formulation in MPC, where the constraint inequalities need to be updated online at every sample, on the basis of the prediction of azimuth angle. In addition, as proved in the study of Lio et al ., the performance differences between the various types of IPCs are negligible. Consequently, single‐blade control IPC is employed in this work, where each blade is equipped with its own controller ( K θ M ) in response to a local blade load measurement.…”
Section: Wind Turbine Modelling and Nominal Robust Feedback Compensatormentioning
confidence: 99%
“…The simulation results in the study of Lio et al . showed that a controller of the form could be designed to be insensitive to such coupling by shaping the open‐loop frequency response to have low gain at the tower frequency. Similar to the plant model, the feedback controller has a discrete‐time state‐space realization: rightxκ(k+1)left=Aκxκ(k)Bκy(k),rightrightu(k)left=Cκxκ(k)Dκy(k), where the state vector xκdouble-struckRnxκ is a collection of variables that characterizes the dynamics of the controller K and the subscript κ denotes controller.…”
Section: Wind Turbine Modelling and Nominal Robust Feedback Compensatormentioning
confidence: 99%
“…Nonetheless, the Coleman transform-based IPC typically targets the static and 3p (thrice per revolution) non-rotating loads caused by the blade (e.g. 0 and 0.6 Hz) [20], whilst tower loads occur mainly at the tower resonant frequency (0.32Hz). Therefore, with a view towards avoiding the undesired couplings, the tower controller is designed as an inverse notch filter with gain concentrated at the tower resonant frequency, away from multiples of the blade rotational frequency:…”
Section: B Estimation-based Controller Designmentioning
confidence: 99%
“…T ∈ R n d are the referred measurements of the flap-wise blade moments, pitch angle signals and wind speeds upon the fixed reference frame, whilst ξ(t) ∈ R n ξ is the projection of the states associated with the blade dynamics upon a non-rotating reference frame (19) and the states of the tower dynamics (20).…”
Section: Transformation To An Lti System and Observability Analysismentioning
confidence: 99%